The projection from the superficial to the deep layers of the superior colliculus: an intracellular horseradish peroxidase injection study in the hamster - Mooney, RD (J Neurosci, 1988)
Intracellular recording and horseradish peroxidase (HRP) injection techniques were employed to examine the projections of superficial layer [stratum griseum superficiale (SGS) and stratum opticum (SO)] superior collicular (SC) neurons in the hamster that sent axon collaterals into the deep laminae (those ventral to the SO) of this structure. Sixty-nine neurons were studied, selected from a sample of over 185 HRP-filled superficial layer cells on the basis of having heavily stained axons. Of the 69 cells included in the study, 43.4% (n = 30) sent at least one axon collateral to the deep laminae. Not all cell types in the superficial layers contributed equally to this interlaminar projection: 78.6% (n = 11) of the recovered wide-field vertical cells, 55.0% (n = 11) of the narrow-field vertical cells, 16.7% (n = 2) of the stellate cells, 40.0% (n = 2) of the marginal cells, 18.2% (n = 2) of the horizontal cells, and 28.6% (n = 2) of neurons we could not classify on the basis of their somadendritic morphology projected to the deep layers. Within a given cell class, there were no significant morphological or physiological differences between the neurons that possessed deep axon collaterals and those that did not. The deep axon collaterals of most of the interlaminar projection neurons were restricted to the stratum griseum intermediate (SGI). In this layer, the largest segment of the axon arbor was located lateral to a projection line that was orthogonal to the SC surface and that passed through the soma of the cell in question. These results, along with those of a previous study (Mooney et al., 1984), which demonstrated that the dendrites of deep layer cells may extend through the SO and into the SGS, indicate that there is an extensive anatomical substrate by which sensory information may be communicated from superficial to deep layer SC neurons.